EFFECT BIOFLOC SYSTEM AND PROBIOTICS Bacillus sp. D2.2 THAT NON SPECIFIC IMMUNE RESPONSE OF TILAPIA Oreochromis niloticus (Linn, 1758) INFECTED BY Aeromonas hydrophila - Triga Royana Sagala; Supono Supono; Esti Harpeni (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Disease in tilapia is caused by Aeromonas hydrophila. The disease has an effect on reduction of production cultivation and economic losses. The control efforts taken are to improve the non specific immune response in tilapia cultivated with biofloc system and probiotics against bacterial infection of Aeromonas hydrophila. This study aims to determine effect the non specific immune response in tilapia cultivated with biofloc system and probiotics against bacterial infection of Aeromonas hydrophila infection. The design used in this study completely randomized design with four treatments, control, biofloc, probiotics in feed and a combination of feed probiotics and biofloc. The parameters observed included total leukocytes, differential leukocyte, survival rate, relative percent survival, and water quality. The results showed that cultivated tilapia with bioflok, probiotics, and a combination of both provides a significant immune response to the parameters of total leukocytes and survival rate compared to control and immune response increases after injected bacteria Aeromonas hydrophila.